2021
DOI: 10.3389/fpsyg.2021.685430
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Impacts Consent Capacity to Treatment in Alzheimer's Disease

Abstract: This study aimed to clarify how behavioral and psychological symptoms of dementia (BPSD) and cognitive function affect the decision-making capacity of persons with Alzheimer's disease (AD) in a real informed consent situation about anti-dementia drug prescriptions. The participants were 76 patients with AD. We used the MacArthur Competence Assessment Tool to assess the capacity for consent to treatment (MacCAT-T). We simultaneously used the Mini-Mental State Examination, Executive Interview, Executive Clock Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…For example, objective risk in experimental studies is similar to the real situation in financial and medical decision-making because the objective risk is presented. Kato et al (2021) demonstrated that understanding and reasoning were impaired in people with AD in a real informed consent situation, which is consistent with an earlier study using hypothetical vignettes ( Moye et al, 2006 ). Therefore, the results of experimental studies are also useful in considering support for decision-making.…”
Section: Limitationsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, objective risk in experimental studies is similar to the real situation in financial and medical decision-making because the objective risk is presented. Kato et al (2021) demonstrated that understanding and reasoning were impaired in people with AD in a real informed consent situation, which is consistent with an earlier study using hypothetical vignettes ( Moye et al, 2006 ). Therefore, the results of experimental studies are also useful in considering support for decision-making.…”
Section: Limitationsupporting
confidence: 89%
“…In medical decision-making, AD patients with apathy and delusions have impaired ability in expression of choice, whereas patients with depression had better performance in this regard ( Bertrand et al, 2017 ), and AD patients with euphoria have a low reasoning performance ( Bertrand et al, 2017 ). Anxiety in patients with AD affected the decision-making capacity in a real informed consent situation ( Kato et al, 2021 ). Thus, the influence of emotion and neuropsychiatric symptoms on decision-making in people with AD is also crucial.…”
Section: Emotion and Neuropsychiatric Symptomsmentioning
confidence: 99%